(untitled) (Journal Of Educational and Psychological Researches, 2022)
Emotions are part of the personality of the individual and affect many different aspects of the personality, and it is an important element of social and psychological adaptation, especially if it is within the limits of nature, and if the methods used to express them are appropriate and moderate. Submission is one of the characteristics that express the way an individual relies upon in dealing with others and in dealing with matters of life. An individual who complies with instructions and orders and abides by them, and performs what is required of him without hesitation or delay. Adolescence is an important and accurate stage in the constructive development of an individual and in his psychological and social life. The current research aims at measuring emotional submission in intermediate school students and exploring the effect of the counseling program in reducing the emotional submission of intermediate school students. Smyth has defined emotional submission as the individual’s involvement in various forms of emotional behavior that is not adapted to the environment, leading to misunderstanding by others. The researcher has constructed the emotional submission scale according to the Beem theory, which consists of (18) items. However, the researcher has used the confrontation method in the counseling program to reduce emotional submission. The research has arrived at those female students in the intermediate school have an emotional submission. In light of the results, the researcher has put forward a number of recommendations and suggestions